AOA Critical Issues Symposium: The Development of an Adaptive Learning Platform in Orthopaedics - Chiodo, Chris; Berg, Marc; Swiontkowski, Marc (Journal of bone and joint surgery. American volume, 2025)
Adaptive learning is a powerful educational tool that uses computer algorithms to personalize and streamline an individual's learning experience. These algorithms allow for continual assessment and real-time customization of the delivery of educational content based on a specific learner's knowledge base; such algorithms mimic a 1-to-1 learning model. The current symposium describes the application of adaptive learning to orthopaedics, as well as the development of an online educational platform that utilizes this promising technology.